Contractor liability for environmental damage resulting from deep seabed mining activities in the area. (April 2020) - Feichtner, Isabel
Abstract: The article focuses on contractor liability for environmental damage under the evolving international law of deep seabed mining. It clarifies that the UN Convention on the Law of the Sea (LOSC) provides not for strict liability, but responsibility for wrongful conduct and that the international law of deep seabed mining does not include a no-harm rule. The article contrasts the international law of deep seabed mining with the Convention on the Regulation of Antarctic Mineral Resource Activities which – unlike LOSC -- did not seek to promote mining, prioritized ecosystem protection, prohibited mining in the absence of adequate information and provided for strict liability of operators. The article then examines the distinction between acceptable harm and inacceptable harm to the environment that constitutes damage. It sketches the obligations of contractors as set out in the mining code and indicates how the gap between responsibility for wrongful conduct and strict liability may be narrowed through far-reaching due diligence obligations. The article addresses 'liability gaps' and ways to fill them, including through mandatory insurance and the establishment of a trust fund. The article ends on a critical note, proposing that – given increasing knowledge about the harmful effects of deep seabed mining on ocean biodiversity -- the social desirability of deep seabed mining should be re-assessed. A liability regime does not render an economic activity socially desirable. Rather it seeks to fairly distribute risks and responsibilities once a hazardous activity has been judged socially desirable despite its risks.